Genetic Analysis and Molecular Breeding Applications of Malting Quality QTLs in Barley - Fang, Yunxia; Zhang, Xiaoqin; Xue, Dawei (Frontiers in Genetics, 2019)
Malting quality is an important determinant of the value of barley grain used in malting and brewing. With recent sequencing and assembling of the barley genome, an increasing number of quantitative trait loci (QTLs) and genes related to malting quality have been identified and cloned, which lays a good molecular genetic basis for barley quality improvement. In this review, we describe the following indicators of malting quality: malt extract (ME), diastatic power (DP), kolbach index (KI), wort viscosity (VIS), free amino nitrogen (FAN) content, soluble protein (SP) content, wort β-glucan (WBG) content, and protein content (PC), and have list related QTLs/genes with high phenotypic variation in multiple populations or environments. Meanwhile, the correlations among the quality parameters and parts of significant indicators suitable for improvement are discussed based on nutrient composition and content required for high-quality malt, which will provide reference for molecular marker-assisted selection (MAS) of malting quality in barley.